Revisiting Marxist Theories in International Relations: Insights from People’s Multiparty Democracy - Rijal, Bishnu (State, Society and Development: PMPD Perspectives, 2025)
Marxism has established itself as one of the world’s most influential ideological frameworks for transformation in power relations. Beyond its role as a political ideology, it holds significant relevance in disciplines such as sociology, anthropology, and literature. Marxism offers a critical perspective for understanding society, devising essential tools for analyzing international relations. Since its inception, it has opposed capitalism and continues to demonstrate its relevance—particularly in an era marked by increasingly exploitative forms of global capitalism. The collapse of communist regimes in Eastern Europe, including the Soviet Union, replicated a major political turning point for Marxist theory. Nonetheless, even its critics cannot ignore its enduring impact on ideological debates and discourses. Regardless of whether Marxism persists in its traditional form, its foundational principles continue to shape the field of international relations. Although Moscow-led communist ideology declined after the 1990s, it was adopted in Nepal by Madan Bhandari in the framework of People’s Multiparty Democracy (PMPD). In qualitative research design, I have examined the intersection of Marxist international relations theory and the PMPD model as implemented by the Communist Party of Nepal (Unified Marxist–Leninist). It critically explores how Marxist principles have been adapted to contemporary political contexts through PMPD, offering a potential alternative to the liberal democratic order in the Global South.